Lower Cretaceous pterosaurs from Colombia. (October 2020) - Cadena, Edwin-Alberto; Unwin, David M.; Martill, David M.
Abstract: The global fossil record of lowermost Cretaceous pterosaurs is meagre, and much of the material is fragmentary. Here we report three occurrences of pterosaurs from the Rosablanca Formation (Valanginian), the first records of this extinct group of flying reptiles from Colombia. Specimens from Zapatoca, Santander Department, consist of fragments of the left mandible and the proximal portion of a wing phalange. A third specimen, from Cundinamarca Department, is the proximal termination of a radius. Although fragmentary, these remains are clearly pterosaurian, on account of their remarkably thin bone walls and provide evidence of pterodactyloids, including a large non-pteranodontian ornithocheiroid, in the northernmost part of South America in the lowermost Cretaceous.